PENGENALAN MANAJEMEN BISNIS SYARIAH DAN KESEHATAN LINGKUNGAN PADA MASA PANDEMI COVID-19 DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Rendi Sugiarto (SAHID EMPOWERMENT JOURNAL, 2022)
This community service activity in 2020 was carried out at the same time to support the government in breaking the chain of the spread of Covid-19. At the same time, sharia business management was introduced to rural communities, especially in Gunung Bunder II Village, Pamijahan District, Bogor Regency. This introduction is by fostering and educating the public regarding sharia business management as well as regarding the dangers of Covid-19 and carrying out a new life in the new normal era. This community service activity begins with observation and initial outreach, program preparation, program implementation, and evaluation. The evaluation results show that this community service activity has contributed to increasing public understanding of sharia business management, Covid-19, awareness to implement health protocols, productive economic activities, and online learning activities during the Covid-19 pandemic.